Design, synthesis, and biological evaluation of small, high-affinity siglec-7 ligands: toward novel inhibitors of cancer immune evasion - Prescher, Horst; Gütgemann, Stephan Alexander; Watzl, Carsten; Brossmer, Reinhard (Journal of medicinal chemistry, 2017)
Natural killer cells are able to directly lyse tumor cells, thereby participating in the immune surveillance against cancer. Unfortunately, many cancer cells use immune evasion strategies to avoid their eradication by the immune system. A prominent escape strategy of malignant cells is to camouflage themselves with Siglec-7 ligands, thereby recruiting the inhibitory receptor Siglec-7 expressed on the NK cell surface which subsequently inhibits NK-cell-mediated lysis. Here we describe the synthesis and evaluation of the first, high-affinity low molecular weight Siglec-7 ligands to interfere with cancer cell immune evasion. The compounds are Sialic acid derivatives and bind with low micromolar Kd values to Siglec-7. They display up to a 5000-fold enhanced affinity over the unmodified sialic acid scaffold αMe Neu5Ac, the smallest known natural Siglec-7 ligand. Our results provide a novel immuno-oncology strategy employing natural immunity in the fight against cancers, in particular blocking Siglec-7 with low molecular weight compounds.